2020
DOI: 10.1111/jac.12397
|View full text |Cite
|
Sign up to set email alerts
|

Harvest interval affects lucerne (Medicago sativa L.) taproot total yield, starch, nitrogen and water‐soluble carbohydrates

Abstract: Lucerne (Medicago sativa L.) has a large taproot to store and release starch, carbohydrates and nutrients during the plant's growth. Recommended management of the lucerne crop aims to keep the taproot stable subject to the demands for feed provision and stand longevity. Field experiments were conducted in Victoria, Australia, to examine the effects of recovery period on taproot mass and nutritive status. Both experiments used established SARDI Seven lucerne crops and were either cut every 21 days (short recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Nearly a century of research has supported the premise that taproot carbohydrate and protein reserves provide C and N for growth and respiration of alfalfa during periods when photosynthesis and N 2 -fixation are reduced by defoliation in summer or other environmental stresses (Graber et al, 1927;Jung and Smith, 1961a;Avice et al, 1996;Volenec et al, 1996;Berg et al, 2018;Mitchell et al, 2020). Numerous studies have also shown that plant nutrition, and in particular P and K fertility, plays a key role in alfalfa growth and stress tolerance (Brown, 1928;Roberts and Olson, 1944;Jung and Smith, 1959;Cooper et al, 1967;Wolf et al, 1976;Kitchen et al, 1990;Volenec et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly a century of research has supported the premise that taproot carbohydrate and protein reserves provide C and N for growth and respiration of alfalfa during periods when photosynthesis and N 2 -fixation are reduced by defoliation in summer or other environmental stresses (Graber et al, 1927;Jung and Smith, 1961a;Avice et al, 1996;Volenec et al, 1996;Berg et al, 2018;Mitchell et al, 2020). Numerous studies have also shown that plant nutrition, and in particular P and K fertility, plays a key role in alfalfa growth and stress tolerance (Brown, 1928;Roberts and Olson, 1944;Jung and Smith, 1959;Cooper et al, 1967;Wolf et al, 1976;Kitchen et al, 1990;Volenec et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the cumulative herbage production, over 18 months, of 42 day cutting intervals (LR) was greater than that of 21 day cutting intervals (SR) by 30% at Hamilton and 40% at Rutherglen. Mitchell et al [18] provided evidence that this reduction in productivity with shorter cutting intervals was associated with a disruption in the energy cycling between shoots and roots.…”
Section: Discussionmentioning
confidence: 99%
“…The inference from this is that there are strong physiological processes in the lucerne plant that make it resilient to more frequent defoliation in terms of survival. This resilience in terms of plant survival is much greater than its general resilience in terms of growth and occurs despite the major disruption of energy cycling between roots and shoots [18] and shoot dynamics [8]. This resilience relates to the plant's intrinsic tolerance to defoliation and includes factors such as increased photosynthetic rate after grazing, high relative growth rates, increased branching or tillering after apical dominance has been disrupted, pre-existing high levels of carbon storage in roots for allocation to above-ground growth and the ability to move carbon stores from the roots to the shoots after defoliation and the availability of residual meristems [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As was reported in Medicago sativa, total or partial removal of the photosynthetic area results in the mobilization of C and N reserves from roots to shoots generating an inversion of source and sink organs (Teixeira et al 2007). The management system imposed and specially the defoliation periods will affect the patter of reserves accumulation and subsequent regrowth (Vignolio et al 2018;Mitchell et al 2020). After shoot removal, regrowth of the new shoots in L. tenuis plants must be supported by non-structural carbohydrates along with N compounds (such as proteins and amino acids) stored in the taproots (Striker et al 2011), specially during early regrowth (Avice et al 1996).…”
Section: Parameters For the Determination Of The Bnf By Lotus Tenuismentioning
confidence: 99%